2018
DOI: 10.1002/ange.201711602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Covalent Chemistry within Biphenyl Scaffolds: Reversible Covalent Bonding, Control of Selectivity, and Chirality Sensing with a Single System

Abstract: Axial chirality is ap revalent and important phenomenon in chemistry.H erein we report ac ombination of dynamic covalent chemistry and axial chirality for the development of av ersatile platform for the binding and chirality sensing of multiple classes of mononucleophiles.A ne quilibrium between an open aldehyde and its cyclic hemiaminal within biphenyl derivatives enabled the dynamic incorporation of ab road range of alcohols,t hiols,p rimary amines,a nd secondary amines with high efficiency.S electivity towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…[4][5][6] In addition, long reaction times and organic solvents are often needed for these sensors which cannot be easily recovered. [7] Host-guest chemistry is an alternative method to expand the substrate scope of CD-based chiroptical sensing.F or example,B iedermann and Nau [8] have reported that the complexes of cucurbit [8]uril with dicationic dyes can be applied in chiroptical sensing of av ariety of biological molecules and drug molecules in water. This strategy is general in terms of functional groups but limited to molecules with an aromatic group next to their chiral centers.A cyclic cucurbit[n]urils and molecular tweezers, [9] pillar[n]arenes, [10] calix[n]arene, [11] resorcinarene, [12] covalent cage molecules, [13] foldamers, [14] and helicates [15] with aromatic sidewalls have also been demonstrated as chirality sensors.But the guests are still limited to aromatic compounds,c harged organic compounds,o rr igid molecules.M olecular sensors with aw ide substrate scope still remain to be developed for optical chirality sensing.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In addition, long reaction times and organic solvents are often needed for these sensors which cannot be easily recovered. [7] Host-guest chemistry is an alternative method to expand the substrate scope of CD-based chiroptical sensing.F or example,B iedermann and Nau [8] have reported that the complexes of cucurbit [8]uril with dicationic dyes can be applied in chiroptical sensing of av ariety of biological molecules and drug molecules in water. This strategy is general in terms of functional groups but limited to molecules with an aromatic group next to their chiral centers.A cyclic cucurbit[n]urils and molecular tweezers, [9] pillar[n]arenes, [10] calix[n]arene, [11] resorcinarene, [12] covalent cage molecules, [13] foldamers, [14] and helicates [15] with aromatic sidewalls have also been demonstrated as chirality sensors.But the guests are still limited to aromatic compounds,c harged organic compounds,o rr igid molecules.M olecular sensors with aw ide substrate scope still remain to be developed for optical chirality sensing.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptional potential of chiroptical sensing with circular dichroism (CD) probes was noticed early on by Berova and Nakanishi, who published several seminal papers with broadly useful zinc porphyrin tweezer hosts . Their outstanding work has spurred the development of a wide variety of CD sensor designs by Borhan, Canary, Anslyn, our group, and others …”
Section: Introductionmentioning
confidence: 99%
“…In addition, stereodynamic probes that undergo irreversible covalent bond formation with a chiral analyte to generate a CD signal that can be used for absolute configuration and ee determination have been developed by several groups . Nevertheless, reversible Schiff base formation with chiral amines has become a very popular and highly successful CD sensing strategy . We now wish to report a highly practical method that allows chiroptical ee analysis of a wide range of amines and amino alcohols using an inexpensive commercially available benzaldehyde derivative as probe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations